ANALISIS PENGALAMAN AUDIT TERHADAP PERTIMBANGAN AUDITOR DIMANA KREDIBILITAS KLIEN SEBAGAI VARIABEL MODERATING (STUDI KASUS PADA KAP DI BATAM DAN MEDAN) - Natalia, Erni Yanti; Harahap, Baru (Jurnal Akuntansi (Media Riset Akuntansi & Keuangan), 2017)
This study aims to analyze the effect of audit experience on auditors judgment withclients credibility as a moderating variable. This research took the population ofPublic Accounting Firm (KAP) in Batam and Medan city, there are 5 KAP in Batamand 21 KAP in Medan. Sample technique used is saturated sampling technique. Thedata used in this study is the primary data, which is done by distributingquestionnaires to respondents in several KAP via email, google forms, via post andshared directly. The questionnaires which are collected and used to analysis dataare 72 questionnaires. The method of analysis used in this research is MRA(Moderated Regression Analysis) path analysis. Data were analyzed by theStatistical Package for Social Science (SPSS) version 21, with a significance level(level sig) as 5% (0,05). The results of the research is showed some result finding,there are: (1) the audit experience has no significant effect on the auditors judgment,(2) the clients credibility does not moderate the influence of the audit experience tothe auditors judgment, so it can be concluded that the clients credibility variable isquasi Moderator.